Growth performance and health status of catfish (Clarias gariepinus, Burchell 1822) fed with various levels of dietary organic selenium addition - Hasrah Hasrah; M. Agus Suprayudi; Nur Bambang Priyo Utomo (Jurnal Iktiologi Indonesia, 2016)
This study aimed to determine the effect of organic selenium to growth performance and health status of catfish Clarias gariepinus.The treatments applied was the addition of organic selenium into the diet with different dose, which was 0, 1, 4, and 8 g kg-1 of the diet. The organic selenium concentration in the diet was 0.30, 0.79, 2.26, and 5.79 mg kg-1 . The catfish with an initial body weight of 5.97 ± 0.06 g and stocking density of 150 individuals tank-1 were rearing for 56 days in the cemen tank with a capacity of 300 liters. During the research, the fish were fed thrice a day at 07.00 am, 02.00 pm, and 08.00 pm with number of diet was 3% of body weight. The result showed that additional organic selenium of 2.26 mg kg-1 in dietary was significantly affecting the retention protein, fat and selenium by 34.8±2.9%, 63.9±4.1% and 28.6±1.9%, respectively. Supplementation of organic selenium in the same dose also enhanced the number of white blood cells of 1.60±0.13 cells mm3 ×105 and hemoglobin concentrations of 7.93±0.1 g %. Supplementation of the organic selenium of 2.26 mg kg-1 in dietary can improve the growth performance and health status of catfish. Abstrak Penelitian ini bertujuan untuk mengevaluasi pengaruh selenium organik terhadap kinerja pertumbuhan dan status kese- hatan ikan lele (Clarias gariepinus). Perlakuan empat dosis selenium organik yang ditambahkan dalam pakan yaitu: 0 (kontrol), 1, 4, dan 8 g kg-1 pakan dengan kadar selenium pakan berturut-turut 0,30; 0,79; 2,26 dan 5,79 mg kg-1 . Ikan lele yang digunakan dengan bobot awal rata-rata 5,97+0,06 g, dipelihara dalam 12 bak beton bervolume 300 liter de- ngan kepadatan 150 ekor per bak selama 56 hari. Ikan diberi pakan 3% dari bobot tubuh dengan frekuensi tiga kali se- hari pada pukul 07.00, 14.00, dan 20.00. Percobaan didesain menggunakan rancangan acak lengkap dengan empat per- lakuan dan tiga ulangan. Hasil penelitian menunjukkan bahwa penambahan selenium 2,26 mg kg-1 pakan memberikan pengaruh yang berbeda nyata pada retensi protein, lemak, dan selenium berturut-turut sebesar 34,8±2,9%, 63,9±4,1% dan 28,6±1,9% dibandingkan dengan perlakuan lainnya (p<0,05). Penambahan selenium dengan dosis yang sama juga dapat meningkatkan jumlah sel darah putih sebesar 1,60±0,13 sel mm3 ×105 dan kadar hemoglobin sebesar 7,93±0,1 g %. Penambahan selenium 2,26 mg kg-1 pakan mampu meningkatkan kinerja pertumbuhan dan status kesehatan ikan lele.